Estimation of Fine Root Biomass of Alders Growing on Technosols Using Two Different Methods. Issue 4 (21st February 2019) - Świątek, Bartłomiej; Chodak, Marcin; Pietrzykowski, Marcin
ABSTRACT: Fine roots play an important role in organic matter accumulation in reclaimed mine soils. However, estimation of the increment of fine root biomass is difficult and none of the existing methods is universal. The paper examined two methods for measurement of fine roots biomass increment (FRBI): i) with using the root-ingrowth core method (RIC) and ii) the monolith sampling method (MSC). The study was conducted under alder plantings ( Alnus incana, A. glutinosa and A. viridis ) introduced on technosols at a combustion waste disposal site and a former open-cast sand mine. The FRBI determined using MSC method was significantly lower (33–481 g m −2 yr −1 ) and less variable than the FRBI measured with RIC (85–2317 g m −2 yr −1 ). However, the results obtained with both methods were correlated (r = 0.70, P = 0, 05). Consequently, MSC is better to qualitatively compare the habitats of tree species in terms of their ability to produce fine roots. However, in the initial soils where plants very often produce more fine roots, RIC seems to be more suitable. This method shows the actual ability of trees to produce roots in order to satisfy their life needs when acquiring a new habitat on reclaimed soils. Such information is particularly important in oligotrophic soils where nutrient deficiency may be balanced only by the efficient circulation and decomposition of organic matter (SOM) including the fine roots that die off after each growing season.